2010
DOI: 10.1002/ps.2060
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metribuzin pollution with phosphatidylcholine–clay formulations

Abstract: A reduction in the recommended dose of metribuzin can be achieved by employing PC-clay formulations, which reduces the environmental risk associated with herbicide applications. Moreover, PC and montmorillonite are non-toxic and do not negatively affect the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…It is a pyrethroid insecticide that was used to control numerous insect pests of field crops (Thomson, 1992). Oral ingestion of this chemical caused vomiting, epigastric pain, nausea and coarse muscular fasciculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a pyrethroid insecticide that was used to control numerous insect pests of field crops (Thomson, 1992). Oral ingestion of this chemical caused vomiting, epigastric pain, nausea and coarse muscular fasciculations.…”
Section: Resultsmentioning
confidence: 99%
“…It is a herbicide used both pre and post emergence in crops and has been set up to contaminate groundwater (Undabeytia et al, 2011). It is slightly to moderately toxic to humans by oral, skin or inhalation routes of exposure (EPA, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…This can lead to enhance the free downward movement of metribuzin in soil profile. Recently, Undabeytia et al (2011) [82] confirmed the role of polar groups (amide) in metribuzin in the formation of water bridges via hydrogen bonding with the hydrophilic head of the non-toxic surfactant phosphatidylcholine in clay formulations. Therefore, in the presence of a non-ionic surfactant, such as Brij35at concentrations above its CMC, metribuzin would be captured by micelles, with its polar groups oriented toward the polar head (EO) of the micelles, which would exhibit a strong hydrophilic interaction via hydrogen bonding or dipole-dipole effects.…”
Section: Effect Of Non-ionic Surfactant Brij35 On Metribuzin In Leachatementioning
confidence: 91%
“…Furthermore, the increase in soil organic matter enhances degradation (Khoury et al, 2006). A reduction in the recommended dose of metribuzin can be achieved by employing PC-clay formulations, which reduces the environmental risk associated with herbicide applications (Undabeytia et al, 2011). Educational materials should be developed to inform users about the potential problems that metribuzin poses to groundwater quality, and monitoring programs should be established to further investigate its ecotoxicological effects.…”
Section: Ecotoxicologymentioning
confidence: 99%